Ks. prof. Marek Tomasz Zahajkiewicz (1934-2015) – dyrektor Ośrodka Archiwów Bibliotek i Muzeów Kościelnych KUL - Hamryszczak, Artur (Archiwa, Biblioteki i Muzea Kościelne, 2015)
Rev. prof. Marek Zahajkiewicz was born on 18 February 1934 in Borysław. He died on 25 July 2015 in Lublin. In 1956, he was ordained a priest. In 1965, he began his research work at the Institute of the History of the Church at the Catholic University of Lublin. In 1967, he received his doctorate, in 1977 he became an assistant professor and in 1992 professor. In the years 1978-2006 he ran the Department of the History of the Church in the Middle Ages at the Faculty of Theology at the Catholic University of Lublin. He was also the director of the Institute of the History of the Church at the Faculty of Theology at the Catholic University of Lublin (1983-2004). From 1985 to 2006 he held the post of director of the Institute of Church Archives, Libraries and Museums and he was the chairman of the Journal Council of "Archiwa Biblioteki i Muzea Kościelne". He organized, among other things, several conferences on archives, library science and church museology, and maintained high academic standards of the journal "Archiwa Biblioteki i Muzea Kościelne" after becoming a successor to Rev prof. Stanisław Librowski, the chief editor and founder of the journal.